A new species of the genus Araniella Chamberlin & Ivie, 1942 (Araneae: Araneidae) from south-west China. (2nd January 2016) - Mi, Xiaoqi; Peng, Xianjin
Abstract: A new species Araniella is reported from Yunnan Province, south-west China, named Araniella plicata sp. nov. Morphological descriptions, distributional data, diagnosis and illustrations are provided.